2007
DOI: 10.1149/1.2780979
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Model for the Flooding Behavior of Ultra-thin PEM Fuel Cell Electrodes

Abstract: A quantitative empirical model is applied to explain the onset of cathode flooding behavior of PEM fuel cell membrane electrode assemblies having the ultra-thin 3M NSTF (nanostructured thin film) electrocatalysts and first generation Toray carbon paper gas diffusion layers (GDL). An empirical method is used to define the current density at the onset of cathode flooding, and calculated vapor phase water removal rates at specific water balance conditions are found to give excellent quantitative agreement with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…[ 209,255 ] NSTF electrodes have clearly shown that high current densities can be achieved using only water as the proton conductor. [ 50–52 ] However, since O 2 diffusion through water is slower than through air, excess localized liquid water can limit O 2 diffusion. Muzaffar et al.…”
Section: Ionomer Distributionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 209,255 ] NSTF electrodes have clearly shown that high current densities can be achieved using only water as the proton conductor. [ 50–52 ] However, since O 2 diffusion through water is slower than through air, excess localized liquid water can limit O 2 diffusion. Muzaffar et al.…”
Section: Ionomer Distributionmentioning
confidence: 99%
“…[ 58,59 ] Thin, low‐Pt loaded electrodes have been reported to be more prone to water management problems. [ 50,51,239 ] Hence, it is suggested the O 2 transport limitations are caused by the extended water diffusion pathways to the surface of the catalyst. This hypothesis suggests that thin CLs are more prone to flooding, and as such, water management is a high priority for low Pt loading electrodes.…”
Section: Ionomer Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The 3M approach to MEA fabrication has been the most impressive demonstration to date that a drastic reduction of Pt loading, m pt , is achievable without sacrificing performance, as these MEAs indeed exhibited the highest power performance reported to date 2 . However liquid water removal clearly transpired as the Achilles heel of catalyst layer design 6 . Moreover, the 3M design demonstrated an important principle of catalyst layer operation: liquid water is sufficient as the medium for proton transport in the catalyst layer.…”
mentioning
confidence: 99%